2021
DOI: 10.3390/ijms222413483
|View full text |Cite
|
Sign up to set email alerts
|

Two-Chains Tissue Plasminogen Activator Unifies Met and NMDA Receptor Signalling to Control Neuronal Survival

Abstract: Tissue-type plasminogen activator (tPA) plays roles in the development and the plasticity of the nervous system. Here, we demonstrate in neurons, that by opposition to the single chain form (sc-tPA), the two-chains form of tPA (tc-tPA) activates the MET receptor, leading to the recruitment of N-Methyl-d-Aspartate receptors (NMDARs) and to the endocytosis and proteasome-dependent degradation of NMDARs containing the GluN2B subunit. Accordingly, tc-tPA down-regulated GluN2B-NMDAR-driven signalling, a process pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…tPA also results in reduced numbers of NMDA receptor subtype 2B (NR2B) signaling through endocytosis of NMDA receptors containing NR2B subunits. 66 NR2B subunits are possibly more expressed on inhibitory interneurons, 67 and hence tPA could lead to reduced inhibition. Inhibition is a critical component in shaping spectral tuning curves.…”
Section: Discussionmentioning
confidence: 99%
“…tPA also results in reduced numbers of NMDA receptor subtype 2B (NR2B) signaling through endocytosis of NMDA receptors containing NR2B subunits. 66 NR2B subunits are possibly more expressed on inhibitory interneurons, 67 and hence tPA could lead to reduced inhibition. Inhibition is a critical component in shaping spectral tuning curves.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report shows that NMDARs subunits, src and adaptor/scaffold proteins, which are partners of NMDAR, are part of the MET interactome in neurons [ 17 ]. Recently, we found that a crosstalk exists between MET and NMDAR to control neuronal survival [ 18 ]. Zeng et al have shown that the glutamate NMDA receptor is crucial for metastatic colonization of the brain by breast cancer cells [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, current evidence suggests that GluN2 composition may not be drastically different between synaptic and extrasynaptic sites [ 90 , 113 , 114 , 115 ], again suggesting that the main driving force in the loss of neuroprotection is the activation of extrasynaptic-specific pathways, with subunit composition possibly providing an additive effect. Interestingly, a recent study demonstrated that the two-chain form of tPA (tc-tPA) recruits GluN2B containing NMDARs in a MET receptor tyrosine kinase dependent manner to drive the down regulation of extrasynaptic GluN2B and promote neuroprotection [ 116 ]. It is therefore possible that the downstream consequences of tPA interaction with NMDARs depend on a combination of factors including NMDAR location, composition, and the form of tPA involved (single vs. two chain form).…”
Section: A Critical Role For Ctd Interactions In Acute Excitotoxicitymentioning
confidence: 99%
“…It is therefore possible that the downstream consequences of tPA interaction with NMDARs depend on a combination of factors including NMDAR location, composition, and the form of tPA involved (single vs. two chain form). Of note, tc-tPA was also observed to reduce CTD 2B phosphorylation [ 116 ], as such it would be of interest to probe the role of the CTD in tAP mediated neuroprotection using both ΔCaMKII and CTD KI mouse models.…”
Section: A Critical Role For Ctd Interactions In Acute Excitotoxicitymentioning
confidence: 99%